Pengujian Fungsionalitas Sistem Informasi Perpustakaan Berbasis Web Menggunakan Metode Blackbox Testing Menggunakan Standar ISO/IEC 29119 - Bob Zimazanya; Muhamad Ariq Rizky Supriyatna; Chairul Anwar (PT Jurnal Cendekia Indonesia, 2025)
Manual library data management is still commonly found in educational institutions and often causes problems such as data recording errors, data duplication, and inefficiency in book borrowing and returning transactions. A Web-Based Library Information System was developed to manage library data in a computerized and centralized manner. This study aims to test the functionality of the system using the Blackbox Testing method. The testing techniques applied are Equivalence Partitioning (EP) and Boundary Value Analysis (BVA). The scope of testing includes login modules, book data management, member data management, and borrowing and returning transactions. The testing process refers to the ISO/IEC/IEEE 29119 standard. The test results indicate that most system functions operate according to the specified requirements, making the system feasible to be implemented as a web-based library management solution.